Politics and Society between Elections Public Opinion in India's States - Swaminathan, Siddharth; Palshikar, Suhas (Taylor & Francis, 2021)
Elections are episodic; governance is routine. This book studies patterns in public opinion on politics and society between elections in India. By using the survey data covering 24 Indian states including the National Capital Region of Delhi (NCR), it will serve as State barometers of public opinion. The surveys seek to understand how politics and governance processes are nested in the social and political relationships between citizens inter se and with government functionaries. The book explores citizen perceptions about the social and political universes they inhabit in periods between elections. It examines social attitudes of citizens, friendship ties across social groups, gender roles and relationships; opinions on governance, ease of public service access, the citizen-state interface, and trust in political institutions; and, political attitudes and identity, nationalism, freedom of expression, and populism. This book explores public perceptions of everyday development and governance outcomes that are shaped by how the government functions between elections: how it relates to citizens on a regular basis; how it provides routine public services to them; and how public order is maintained. An incisive study on public opinion on politics, society, and governance in India, this book will be of great interest to scholars and researchers of political science, governance, public policy, and South Asian studies. It will also be of immense interest to bureaucrats, policymakers, think tanks, and organisations working in the areas of development studies, politics, society, and governance.